Pengembangan Media Pohon Pintar untuk Siswa Kelas I MI Tarbiyatul Huda - Ulfa, Nanik; Saffida, Aulia; Chatib, Romadlon (Diksi: Jurnal Pendidikan dan Literasi, 2024)
Learning media in madrasah ibtidaiyah is still very limited, especially in addition and subtraction material. This study aims to produce Smart Tree learning media on Addition and Subtraction Materials in Class I MI Tarbiyatul Huda Arjowinangun Malang City which meets valid and practical criteria. This type of research is development research, the development research model used is the Borg and Gall development model, namely: a) research and collection of initial information, b) planning, c) development of initial product format, d) expert validation test, e) product revision, f) small group trial, g) product revision, h) large group trial, i) final product refinement, j) dissemination, but in this study only until the large group trial stage due to time constraints. Data collection techniques were carried out by researchers using questionnaires, observations, and tests. Based on the results of the study, it was found that the results of layout practicality validation were 96%, material validation was 80%, and 80% media validation. The results of the data analysis of the field trial test showed an increase from the average value of the pretest results was 68.3% and the average post-test was 82.2%. Also obtained are the test results of tcount≥ ttable which is 2.91 ≥ 1.75, meaning Ho is rejected and Ha is accepted. Thus, there is a significant difference in the implementation of the Smart Tree learning media. This shows that the Smart Tree learning media is feasible to use and can improve student learning outcomes.